(B15c5)BiI3(I2): Molecular Benzo-15-Crown-5―BiI3 Complexes Bridged by Iodine Molecules to Chains - Christoph Fiolka; Mark Richter; Ingo Pantenburg; Anja-Verena Mudring; Gerd Meyer (Crystals, 2011)
The reaction of bismuth triiodide with iodine and benzo-15-crown-5 in ethanol/dichloromethane yielded red single crystals of (b15c5)BiI3(I2) (monoclinic, P21/c (no. 14), a = 1376.9(1), b = 1172.7(1), c = 1700.2(2) pm, b = 115.197(6), V = 2484.1(4)·106 pm3, Z = 4). Neutral pseudo-octahedral complexes (b15c5)BiI3 are connected by secondary bonding interactions via iodine molecules to chains. Electronic structure calculations of the neutral complex (b15c5)BiI3 reveal that the compound can indeed be described as b15c5 interacting with a molecular BiI3 unit. However, bonding has to be mainly electrostatic as the interactions of the bismuth 6s lone pair with the 2p orbitals of the oxygen atoms of the crown ether are clearly antibonding.